Examining the Impact of Core Self-Evaluations Personality Model and Leadership Styles on Auditor Performance - Pancawati, Ni Putu Widya; Sujana, I Ketut (E-Jurnal Akuntansi, 2024)
The performance of auditors is a measure of their competence in completing the audit of a company's financial statements. This study aims to explore the influence of locus of control, emotional stability, self-esteem, self-efficacy, and leadership style on auditor performance, framed within attribution theory. The research was conducted at Public Accounting Firms (KAPs) in the province of Bali, as listed in the 2023 directory of the Indonesian Institute of Certified Public Accountants (IAPI). A total of 78 auditor samples were selected from KAPs in Bali using purposive sampling methods. The analytical technique employed was multiple linear regression analysis. The results indicate that locus of control, emotional stability, self-esteem, self-efficacy, and leadership style each have a positive and significant impact on auditor performance. This study contributes to the existing literature by affirming the significant roles these psychological and leadership factors play in enhancing auditor effectiveness, suggesting that fostering these traits could improve audit quality. Keywords: Locus of control, Emotional Stability, Self Esteem, Self Efficacy, Gaya Kepemimpinan, Kinerja Auditor